Security and Vulnerability of SCADA Systems over IP-Based Wireless Sensor Networks - HyungJun Kim (International Journal of Distributed Sensor Networks)
An overview of supervisory control and data acquisition (SCADA) systems is presented and relevant security concerns are addressed. To secure IP-based SCADA systems, it is vital to implement secure architectures which prevent access to the SCADA from corporate IT, in addition to excellent management practices in managing IP-based networks. We give an overall explanation of SCADA systems along with their security concerns and vulnerability. In the case of legacy SCADA systems, the concerns regarding security were minimal since it used proprietary networks; however, since the move of SCADA systems to the Internet, security problems have become an imperative issue, especially problems regarding IP-based systems. We also discuss various forms of threats and vulnerabilities on future SCADA systems applied with IPv6 over low-power, wireless personal area networks (6LoWPANs) and suggest security management methods to overcome these concerns. In order to identify and remove various vulnerabilities and threats to SCADA systems over IP-based wireless sensor networks, especially for 6LoWPAN applications, we examine possible threats and propose proper and precise security management methods.